2014
DOI: 10.15414/jmbfs.2014-15.4.3.203-208
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases Production Under Solid State Fermentation Using Agro Waste as a Substrate and Its Application in Saccharification by Trametes Hirsuta Ncim

Abstract: Food and energy crisis are the biggest constraint all over the world which has focused lights on need of utilizing renewable resources to meet the future demand. A promising strategy is efficient utilization of lignocellulosic waste and fermentation of the resulting sugars for production of desired metabolites or biofuel. Production of all the cellulase enzymes on wheat bran and different parameters regulating it like pH, moisture ratio (substrate: liquid), temperature and inoculum size has been optimized whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Crude cellulase produced from agricultural residues under SSF has been used in the saccharification of lignocellulosic materials such as rice straw, sugarcane bagasse, corn cob, fruits peel, and wheat bran enhanced the sugar yield for bioethanol production [98][99][100]102,103]. The utilization of grass powder as a carbon source in the production of cellulase and hemicellulase by Phanerochaete chrysosporium by SSF yielded an efficient enzyme complex which could be employed for hydrolysis of rice husk.…”
Section: Enzymes Productionmentioning
confidence: 99%
“…Crude cellulase produced from agricultural residues under SSF has been used in the saccharification of lignocellulosic materials such as rice straw, sugarcane bagasse, corn cob, fruits peel, and wheat bran enhanced the sugar yield for bioethanol production [98][99][100]102,103]. The utilization of grass powder as a carbon source in the production of cellulase and hemicellulase by Phanerochaete chrysosporium by SSF yielded an efficient enzyme complex which could be employed for hydrolysis of rice husk.…”
Section: Enzymes Productionmentioning
confidence: 99%
“…A fungal strain, Alternaria alternate was accounted for maximum cellulase production at 35°C under SSF [57], which was consistent with our observation. Although, Maurya et al [58] and Bhaumik et al [59] reported 30°C as optimum for maximum cellulase production under SSF by Trichoderma reesei and Trametes hirsute, respectively. Whereas, thermophilic B. licheniformes gave the best result for cellulase production at 50°C under submerged fermentation conditions.…”
Section: Effect Of Different Temperaturementioning
confidence: 99%